För Sverige i framtiden: Bio-objektifiering av ny medicinsk teknologi (Sociologisk Forskning, 2013)
Taking Sweden into the future – Bio-objectification of new medical technologyIn this article, we analyze how contemporary discursive silences around new biotechnologies such as cybrids and induced pluripotent stem cells (iPSC), have been enabled by earlier policy processes in the area, e.g. boundary work around what is human and non-human, living and non-living, subject and object. The analysis of policy processes around xenotransplantations and the use of human embryonic stem cells, shows that the stem cells’ and xenografts’ “bio-identities” become stabilized through high expectations for the future, a lack of therapeutic possibilities and struggles over definitions of life. The policy processes around human embryonic stem cells and organs from other animals, are characterized by a normalization of certain understandings of ”life”, trust in scientific progress and it’s national financial potentials and a categorization of criticism as irrational. Through these “bio-objectification processes”, debate and decision making has been moved from a political and public context into ethical committees and research funding bodies. The article concludes by discussing consequences of this political non-handling of biomedical technologies and how these bioobjects could be re-politicized.
Keywords: Bio-technology; policy; stem cells; xeno transplantation; cybrid; discourse analysis; bio-object; bio-identity